2018
DOI: 10.3390/horticulturae4030016
|View full text |Cite
|
Sign up to set email alerts
|

Growth, Water-Use Efficiency, Stomatal Conductance, and Nitrogen Uptake of Two Lettuce Cultivars Grown under Different Percentages of Blue and Red Light

Abstract: The objective of this study was to characterize growth, water-use efficiency (WUE), stomatal conductance (g s ), SPAD index values, and shoot nitrogen uptake of two lettuce cultivars grown under different percentages of blue and red light. The treatments evaluated were 100% red; 7% blue + 93% red; 26% blue + 74% red; 42% blue + 58% red; 66% blue + 34% red; and 100% blue. Broad-spectrum (19% blue, 43% green, and 38% red) light was used to observe the effects of wavelength interactions. All of the treatments pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 52 publications
(89 reference statements)
5
35
0
1
Order By: Relevance
“…Amoozgar 36 reported monochromatic red light to increase leaf concentration of K, P and Fe in lettuce, while a mixed RB radiation enhanced N and Mg concentration in leaf tissues. However, Clavijo-Herrera 37 demonstrated that N accumulation in lettuce leaves did not vary in response to changes in the RB ratio of the incident light, as was also shown for our experiments. Some indications on nutrients concentration in shoot tissues are available for other plant species, with studies addressing the role of red and blue radiation in P, K, Ca, Mg and Fe concentrations in broccoli microgreens 38 .…”
Section: Resultssupporting
confidence: 89%
“…Amoozgar 36 reported monochromatic red light to increase leaf concentration of K, P and Fe in lettuce, while a mixed RB radiation enhanced N and Mg concentration in leaf tissues. However, Clavijo-Herrera 37 demonstrated that N accumulation in lettuce leaves did not vary in response to changes in the RB ratio of the incident light, as was also shown for our experiments. Some indications on nutrients concentration in shoot tissues are available for other plant species, with studies addressing the role of red and blue radiation in P, K, Ca, Mg and Fe concentrations in broccoli microgreens 38 .…”
Section: Resultssupporting
confidence: 89%
“…The accumulation of Fe, P, Mg, and N in lettuce tissues was significantly increased by either R or a mixture of R and B (R:B = 2), while the accumulation of K and Ca increased under B light [ 47 ]. However, no differences in N accumulation in lettuce leaves were found among monochromatic B or R lights or mixtures of R and B at varying ratios (e.g., R:B = 0.5, 1, 3, and 13) [ 48 ]. In general, B light could affect proton pumping, membrane permeability, and ion channel activities in plants [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the results of this study with respect to increase in the area of leaves, same results were reported in leaves of lettuce, radish, soy, wheat and roses with the application of both the blue and red lights (Stutte et al., 2009; Samuolienė et al., 2011; Cope and Bugbee, 2013; Terfa et al., 2013). Given the examinations conducted on lettuce, those plants that did not receive any blue light had a smaller area of leaves compared to plants that received even small extents of blue light, with 66% increase in the area of leaves (Clavijo-Herrera et al., 2018). In general, if exposure to light results in biochemical and physiological changes in plants, then these changes can be associated with changes in morphological and anatomic structure of leaves, particularly the anatomic components of leave (Puglielli et al., 2017).…”
Section: Discussionmentioning
confidence: 99%